Local recurrence after curative surgical treatment of renal cell cancer: a study of 91 patients - Du, YueJun; Grüllich, Carsten; Hadaschik, Boris; Hatiboglu, Gencay; Hohenfellner, Markus; Pahernik, Sascha (Clinical genitourinary cancer, 2016)
Background Local recurrence (LR) after curative therapy for renal cell cancer is a rare event, and surgery is still the primary treatment option. Patients and Methods This was a single-institution, single-arm retrospective study from a prospectively conducted database. A total of 91 patients with a median age of 63.0 years (interquartile range, 57.5-68.3), who had undergone LR resection after initial curative treatment of RCC were enrolled. The time to LR (TTLR) was defined as the interval from primary curative surgery to LR. Cancer-specific survival, overall survival, and progression-free survival were evaluated after LR resection. Statistical analyses of the clinical and pathologic variables were performed using Cox regression analysis and the Kaplan-Meier method. Results The median time to LR was 29.8 months (interquartile range, 10.8-64.3). On multivariate analysis, age > 65 years, T3/T4 stage, Fuhrman grade 3/4, major venous infiltration, and positive surgical margins were related to early LR after primary curative surgery. LR size of ≤ 7 cm and TTLR of > 24 months were associated with longer cancer-specific survival. Furthermore, patients with a TTLR of > 24 months had better overall survival and progression-free survival. Of the entire cohort, intraoperative radiation therapy and targeted therapy were used in 17 (18.7%) and 15 (16.5%) patients, respectively. Conclusion Advanced age, T3/T4 stage, Fuhrman grade 3 or 4, major venous infiltration, and positive surgical margins at primary tumor resection were related to a greater risk of early LR. An LR size of ≤ 7 cm and TTLR of > 24 months were associated with favorable oncologic outcomes after LR resection. Thus, patients who present with a longer TTLR and smaller LR size, along with favorable features at primary tumor resection, will benefit from surgical treatment.
Gesehen am 29.11.2018